Intensity of religious cues in Islamic financial products: Exploring the role of Religiosity and Self-reference - Ameen-Ud-Din (2016)
Despite the continuous increase in the intensity of religious imagery in advertising, a limited body of literature has tried to explore the influence of such efforts on consumer evaluations. Extant research investigated religious symbols in isolation from other relevant religious appeals while focusing only on Christian religious groups. This research set out to investigate how the subsequent increase in the intensity of religious cues in an advertisement impact consumers’ attitudes towards the advertisement, the brand and purchase intention while taking into account Muslim consumers. Consumers’ level of religiosity and self-reference are also taken into account to test how they interact with consumer attitudes in this advertising phenomenon. This research is carried out in a context where not only the communication but also the product used in the advertisement is congruent to the religious beliefs of the audience. A structured questionnaire along with an experimental stimulus was designed to elicit consumer attitudes, level of religiosity and self-reference. Findings from the data revealed significant increase in attitude towards the advertisement and purchase intentions with increasing intensity of religious cues until a point after which both these attitudes started decreasing. Also, moderate level of religious appeals were found suitable for highly religious individuals while high intensity appeals were effective for individuals with low level of religiosity in changing attitude towards the advertisement. This study found no influence of religious appeals on attitude towards the brand and self-reference. Therefore, marketers need to carefully consider the use of religious appeals as this study suggests that overuse of such appeals may induce negative responses.